International cooperation and challenges: Understanding cross-cultural issues in the processes of accident investigation - Li, Wen-Chin; Young, Hong-Tsu; Wang, Thomas; Harris, Don (Cranfield University, 2007)
The idea that national cultural characteristics play a part in aviation safety had been suggested by Helmreich & Merritt (1998). This research involved around 45 aviation accident investigators from different cultural backgrounds and investigated attribution of causal factors in the Ueberlingen accident report through the application of the Human Factors Analysis and Classification System (Wiegmann & Shappell, 2003). Hofstede’s (1991 & 2001) cultural dimensions draw a clear picture of the attributable patterns of human errors based on cultural differences. As a result it is necessary to develop a better understanding of the differences in attribution of accident causes and contributory factors across cultures to promote both aviation safety and international cooperation for accident investigation will be achieved. Furthermore, when suggesting safety enhancements resulting from accident investigations it needs to be noted that the same remedy may not work in different cultures. Remedial actions must be 'culturally congruent'. This process starts with understanding the cultural factors at work in the accident investigation process itself.
Keywords: Accident Investigation, Cross-cultural issues, Human Factors